Re-enchanting research: Using narrative in antiracism education - Elizabeth Carriere (Adult Education Research Conference, 1994)
"Does it sag like a heavy load? Or does it explode?". This syncopated question, quoted in Studs Terkel’s book, Race (1992), and the truncated narrative of which it is a part, are fragments of a vast and hidden discourse about what racism means to people. Is there a role for these understandings of racism in the design and teaching of antiracism to adults? In this paper I develop a case for reclaiming narrative domains of the everyday as a focus for research in education. I argue that narratives, stories which resonate with particularities of lived experience (Lyotard, 1992), can be divined in both formal scientific theory, as well as in people’s descriptions of their lives. An emphasis on stories as media for social analysis is counterpoint to the way modernist theory silences narrative as an 'unusable' base for knowledge (De Certeau, 1988). Deconstructing, or 'unpacking' theoretical works through critical reading, however, reopens them as highly narratized texts, replete with imagery, nuance and seductive devices to arouse the commitment of readers. Whether ideas about racism are expressed in theoretical texts or through people's everyday experience, such reading can make visible the dynamics of contestation, resistance, difference, jouissance, play and contingency, which can be used to emancipatory effect in antiracism education. The following pages present highlights of an argument for re-enchanting and re-enlivening research by 'reading', as narrative, ocial dynamics of theorizing about racism.